Myoid differentiation in dermatofibrosarcoma protuberans and its fibrosarcomatous variant: 10 years' experience in a tertiary hospital - Chun-hai Lo; Po-man Tsang; Shui-ying Cheng (University of São Paulo, 2022)
Dermatofibrosarcoma protuberans (DFSP) is a relatively rare, locally aggressive, and dermal-based fibroblastic tumor. There are several histological variants, in which the usual emphasis is on fibrosarcomatous DFSP, as it acquires metastatic potential. Myoid differentiation in DFSP is rare, and more often found in fibrosarcomatous DFSP. Myoid differentiation is defined as tumor cells with brightly eosinophilic cytoplasm, well-defined cytoplasmic margins, and vesicular nuclei. In this study, we aim at characterizing the immunostaining pattern regarding myoid differentiation in DFSP, and discuss the potential pitfall in making the diagnosis. A total of ten cases of DFSP were found in the past ten years in our hospital. Two of them show focal myoid differentiation, including the only case of fibrosarcomatous DFSP. Around 5% of the tumor area in the traditional DFSP case shows myoid differentiation, while around 10% of the tumor area in fibrosarcomatous DFSP shows myoid differentiation. The myoid areas show positive staining, albeit patchy to focal, for smooth muscle markers, including smooth muscle actin, muscle-specific actin, caldesmon, and calponin. Staining for CD34, in those areas, is weak or negative. This may create diagnostic difficulty with smooth muscle tumors or myofibroblastic lesions, especially in a small biopsy sample. In difficult cases, the detection of COL1A1-PDGFB fusion by fluorescence in situ hybridization is helpful, as this is a characteristic chromosomal translocation found in the large majority of DFSP.